Digital Smile Makeover: A Multidisciplinary Team Approach - Nourah, Dalia (European Journal of Dentistry, 2023)
Aesthetics is a fundamental part of contemporary dental practice. A pleasant smile depends on the gingival tissue architecture and dental characteristics. Excessive gingival display (gummy smile) is considered an unattractive smile and can affect a person's confidence. There are many etiological factors related to a gummy smile. Aesthetic rehabilitation of these cases often requires an interdisciplinary approach and close collaboration between dental specialties. This article describes an approach to excessive gingival display management caused by short teeth and hyperactive lips using a digital workflow for crown lengthening. A digital approach enables predictable planning and decreases the need for postsurgical modifications, thus shortening the treatment duration. Computer software is used for planning and 3D-printed guide for crown lengthening and implant placement. Two months later, lip repositioning was performed to reduce the hyperactive lip. After 4 months, prosthetic treatment and Botox injections were done to restore an aesthetic smile.
Keywords: gummy smile; crown lengthening; digital technology; lip repositioning